Guanabenz Interferes with ER Stress and Exerts Protective Effects in Cardiac Myocytes - Neuber, Christiane (Public Library of Science, 2014)
Endoplasmic reticulum (ER) stress has been implicated in a variety of cardiovascular diseases. During ER stress, disruption of the complex of protein phosphatase 1 regulatory subunit 15A and catalytic subunit of protein phosphatase 1 by the small molecule guanabenz (antihypertensive, α(2)-adrenoceptor agonist) and subsequent inhibition of stress-induced dephosphorylation of eukaryotic translation initiation factor 2α (eIF2α) results in prolonged eIF2α phosphorylation, inhibition of protein synthesis and protection from ER stress. In this study we assessed whether guanabenz protects against ER stress in cardiac myocytes and affects the function of 3 dimensional engineered heart tissue (EHT). We utilized neonatal rat cardiac myocytes for the assessment of cell viability and activation of ER stress-signalling pathways and EHT for functional analysis. (i) Tunicamycin induced ER stress as measured by increased mRNA and protein levels of glucose-regulated protein 78 kDa, P-eIF2α, activating transcription factor 4, C/EBP homologous protein, and cell death. (ii) Guanabenz had no measurable effect alone, but antagonized the effects of tunicamycin on ER stress markers. (iii) Tunicamycin and other known inducers of ER stress (hydrogen peroxide, doxorubicin, thapsigargin) induced cardiac myocyte death, and this was antagonized by guanabenz in a concentration- and time-dependent manner. (iv) ER stressors also induced acute or delayed contractile dysfunction in spontaneously beating EHTs and this was, with the notable exception of relaxation deficits under thapsigargin, not significantly affected by guanabenz. The data confirm that guanabenz interferes with ER stress-signalling and has protective effects on cell survival. Data show for the first time that this concept extends to cardiac myocytes. The modest protection in EHTs points to more complex mechanisms of force regulation in intact functional heart muscle.